Debit Cards Payment Behaviour of Consumers at Bhat-Bhateni Supermarket and Department Store in Kathmandu - Karanjit, Shrishna (Journal of Business and Social Sciences Research, 2018)
This paper attempts to identify the different factors affecting consumers on adoption of debit cards with reference to Bhat-Bhateni Supermarket and Department Store (BSDS) in Kathmandu Valley. A month long survey was conducted among the consumers of Kathmandu, who shopped at BSDS in which 175 respondents were interviewed using convenient sampling. For the purpose of study, two models were devised considering both debit card users and non debit card users. The study showed higher preference and interest among the consumers in using debit cards than cash while making payments. The results also showed that the debit payment behavior among customers varied across nationality and income. Further, it revealed that the most significant factors influencing the debit payment behavior were perceived ease of use and usefulness of the card among others.Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 80-88